The role of board dynamics in explaining payout policy and shareholders' wealth: Evidence from the banking sector in Africa - Daniel Ofori-Sasu; Gloria Clarissa Dzeha; Christopher Boachie; Joshua Yindenaba Abor (Research in Globalization, 2022)
The paper investigates the role of board dynamics in explaining the effect of payout policy on shareholders' wealth creation at the market and bank levels. The study employs the 2SLS estimation of a panel dataset of 528 banks from 29 African countries from the year 2006 to 2018. The study finds that board dynamics enhance payout policy. The study shows that board dynamics create market and bank-level wealth to shareholders. Further, payout policy reduces shareholders' wealth creation in the market but increases bank-level wealth of shareholders. The study finds that payout policy can be utilized as a substitute control device in the presence of board governance mechanism in order to protect shareholders' wealth. In general, the marginal effect of payout policy on shareholders' wealth creation conditioned on board dynamics is relatively stronger at the market level compared to the bank level.
Keywords: 330; Board dynamics; Payout policy; Shareholder's wealth creation